Deletion of NRF2 disturbs composition, morphology, and differentiation of the murine tail epidermis in chronological aging - Sochorová, Michaela; Kremslehner, Christopher; Nagelreiter, Ionela-Mariana; Ferrara, Francesca; Lisicin, Maja Mitrovic; Narzt, Marie-Sophie; Bauer, Christina; Stiegler, Alexandra; Golabi, Bahar; Vávrová, Katerina; Gruber, Florian (BioFactors (Oxford, England), 2023)
NRF2 is a master regulator of the cellular protection against oxidative damage in mammals and of multiple pathways relevant in the mammalian aging process. In the epidermis of the skin NRF2 contributes additionally to the formation of an antioxidant barrier to protect from environmental insults and is involved in the differentiation process of keratinocytes. In chronological aging of skin, the capacity for antioxidant responses and the ability to restore homeostasis after damage are impaired. Surprisingly, in absence of extrinsic stressors, NRF2 deficient mice do not show any obvious skin phenotype, not even at old age. We investigated the differences in chronological epidermal aging of wild type and NRF2-deficient mice to identify the changes in aged epidermis that may compensate for absence of this important transcriptional regulator. While both genotypes showed elevated epidermal senescence markers (increased Lysophospholipids, decreased LaminB1 expression), the aged NRF2 deficient mice displayed disturbed epidermal differentiation manifested in irregular keratin 10 and loricrin expression. The tail skin displayed less age-related epidermal thinning and a less pronounced decline in proliferating basal epidermal cells compared to the wildtype controls. The stratum corneum lipid composition also differed, as we observed elevated production of barrier protective linoleic acid (C18:2) and reduced abundance of longer chain saturated lignoceric acid (C24:0) among the stratum corneum fatty acids in the aged NRF2-deficient mice. Thus, despite epidermal differentiation being disturbed in aged NRF2-deficient animals in homeostasis, adaptations in keratinocyte proliferation and barrier lipid synthesis could explain the lack of a more severe phenotype.
Keywords: buněčná diferenciace; savci; Epidermal Cells; Keratinocytes; NF-E2-Related Factor 2; stárnutí; keratinocyty; Tail; Antioxidants; zvířata; Mammals; myši; Aging; Mice; Epidermis; antioxidancia; NRF2; skin; Cell Differentiation; faktor 2 související s NF-E2; Animals; aging; lipid; epidermis; epidermální buňky; ocas